2006
DOI: 10.1682/jrrd.2005.08.0135
|View full text |Cite
|
Sign up to set email alerts
|

Interface pressure and cutaneous hemoglobin and oxygenation changes under ischial tuberosities during sacral nerve root stimulation in spinal cord injury

Abstract: Abstract-Noninvasive functional magnetic stimulation (FMS)of the sacral nerve roots can activate gluteal muscles. We propose the use of sacral anterior root stimulator (SARS) implants to prevent ischial pressure ulcers in the spinal cord injury (SCI) population. In this study, we (1) investigated the acute effects of sacral FMS on ischial pressure, skin blood content, and oxygenation changes in people with SCI and demonstrated the utility of FMS as an assessment tool, and (2) showed that similar effects are po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 34 publications
(39 reference statements)
1
23
0
Order By: Relevance
“…[7][8][9][10][11] Levine et al 8,9 used surface ES in the gluteal muscles of individuals with an SCI and found a changed buttock tissue shape 8 and increased muscle BF. 9 Ferguson et al 7 stimulated the quadriceps muscles and found a decrease in interface pressure as well.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] Levine et al 8,9 used surface ES in the gluteal muscles of individuals with an SCI and found a changed buttock tissue shape 8 and increased muscle BF. 9 Ferguson et al 7 stimulated the quadriceps muscles and found a decrease in interface pressure as well.…”
Section: Introductionmentioning
confidence: 99%
“…A combination of this specialized cushion for pressure reduction and pressurerelief movements, in which the wheelchair user performs "push-ups" or "forward leans," is considered the best option for PU prevention in people with SCI [10][11][12][13]. However, pressure-relief movements require good upper-limb strength and continued motivation, which are not always present in people with high-level lesions [14]. The incidence of PUs remains unacceptably high [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…For the individual characterization of the mechanical pressure of the wheelchair cushion, the measure of the interface pressure between the person and the seating surface is the most common test performed in clinical settings [14,[19][20]. However, the mechanical properties are not the only characterizations that indicate the risk of tissue damage.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations